Temporal variation of fish and shrimp assemblages in Merbok River Estuary, Tanjung Dawai, Kedah, Malaysia - Sarker, S. M. Nurul Amin Harmuj Ali; Arshad, Aziz (2013)
The temporal variation and assemblage composition of fish and shrimp species caught by estuarine set bag nets(ESBN) in Tanjung Dawai estuarine, Tanjung Dawai, Kedah, Malaysia were investigated based on data collected from May to September 2012. Stolephorus tri was the most abundant fish caught by ESBN in Tanjung Dawai (1.1%), while Acetes sp. was the most abundant shrimp (92.18%). The highest percentage of species occurrence caught by ESBN in Tanjung Dawai estuary was found in August (70.0%), and the lowest was in May (50%). The percentage of numerical abundance of all fish and shrimp species caught by ESBN was the highest in July (51.17%) and the lowest in August (7.04%). Length-weight relationship analysis displayed that four species had a positive allometric growth while seven of them had a negative allometric growth. The average monthly catch per unit effort (CPUE) of the ESBN observed was 2.914 kg net-1 hour -1 Since the abundance percentage of juvenile fish caught by ESBN was low (2.42%), the use of ESBN in Tanjung Dawai estuarine, Merbok River, Kedah was concluded to be a non-destructive fishing gear.